Extensión universitaria, un proyecto académico. Reflexiones para la discusión (2002)
ABSTRACT: Extension was included long time ago as one of the activities in the institutions of higher education. Nevertheless, its acceptance as primordial function, function just recently has taken a place among them. One of the most important difficulties is possibly due to a lack of clarity about the meaning given to the activities of extension by academics, institutional directors and other members of the university. This article derives from a lecture given at the Iberoamerican Congress for the extension at the universities, in in São Paulo, Brazil, 2001, it presents for discussion, name conceptual references on the primordial function of extension and the academic dimension as fundamental and given true sense to this academic responsibility. Previous to the anterior exposure, it makes a synthesis on antecedents of extension in a public university, describes some common fragilities in routine activities, and intents some answers to essence seen from the perspective of its mission. This paper shares a referential framework to orientate politics on extension, according to the concept developed, and presents ways to implemented in the relation university-society. The article concludes applying the extension to the health areas, illustrated with the experiences at the University of Antioquia.